Regulation of FGF10 Signaling in Development and Disease - Watson, Joanne; Francavilla, Chiara (Frontiers in Genetics, 2018)
Fibroblast Growth Factor 10 (FGF10) is a multifunctional mesenchymal-epithelial signaling growth factor, which is essential for multi-organ development and tissue homeostasis in adults. Furthermore, FGF10 deregulation has been associated with human genetic disorders and certain forms of cancer. Upon binding to FGF receptors with heparan sulfate as co-factor, FGF10 activates several intracellular signaling cascades, resulting in cell proliferation, differentiation, and invasion. FGF10 activity is modulated not only by heparan sulfate proteoglycans in the extracellular matrix, but also by hormones and other soluble factors. Despite more than twenty years of research on FGF10 functions, context-dependent regulation of FGF10 signaling specificity remains poorly understood. Emerging modes of FGF10 signaling regulation will be described, focusing on the role of FGF10 trafficking and sub-cellular localization, heparan sulfate proteoglycans, and miRNAs. Systems biology approaches based on quantitative proteomics will be considered for globally investigating FGF10 signaling specificity. Finally, current gaps in our understanding of FGF10 functions, such as the relative contribution of receptor isoforms to signaling activation, will be discussed in the context of genetic disorders and tumorigenesis.